PERTUMBUHAN TANAMAN KEDELAI (GLYCINE MAX L.) HASIL RADIASI SINAR GAMMA CESIUM-137 - Nuraeni Nuraeni; Hernawati Hernawati; Sefrilita Risqi Adikaning Rani; M. Said L; Ananda Anindia Putri (JOURNAL ONLINE OF PHYSICS, 2023)
The study of the Effect of Cesium-137 Gamma Ray Radiation on the Growth of Soybean Plants (Glycine max L.) aims to determine the quality of growth of soybean plants (Glycine max L.). The Cesium-137 source was used as a source of irradiation in the study, with a constant distance (x) of irradiation of 100 cm from the wall, with dose variations of 0 Control, 25 mGy, 50 mGy, 75 mGy, 100 mGy and 120 mGy. The method used in this research is descriptive statistical analysis. The samples used in this research are soybean seeds from the Langkowa Soybean plantation, Tonasa Village, Tombolopao Subdistrict and packaged soybeans taken from the packaging seeds of Flower Seed Shop Jl. Veteran Selatan No.395. The results of this study showed that the sprout growth time with a dose treatment of B5 (75 mGy) took 9 days to grow, the percentage of stem height (cm) at a dose of B5 (75 mGy) the average stem height was 3.7 cm, the percentage of leaf width (cm) at a dose of B4 (100 mGy) the average leaf width was 2.9 cm, the percentage of the number of leaves (sheets) at a dose of B3 (75 mGy) the average number of leaves was 4 sheets. The use of Cesium-137 and Cobalt-60 Gamma radiation in plant breeding can be utilised on various types of plants to increase plant cultivation and better production results.